(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Zhurba L. V. The typification and methods of development of newest history’s problem exercises The methodical recommendation for several types of problem exercises from newest history are proposing at the article. The author analyzes the approaches of scientists to the definition of «challenging task»; considered indicators and ways to create problematic situations.